CoverageTool: A semi-automated graphic software: applications for plant phenotyping - Merchuk-Ovnat, Lianne; Ovnat, Zev; Amir-Segev, Orit; Kutsher, Yaarit; Saranga, Yehoshua; Reuveni, Moshe (Plant methods, 2019)
Characterization and quantification of visual plant traits is often limited to the use of tools and software that were developed to address a specific context, making them unsuitable for other applications. is flexible multi-purpose software capable of area calculation in cm , as well as coverage area in percentages, suitable for a wide range of applications. Here we present a novel, semi-automated and robust tool for detailed characterization of visual plant traits. We demonstrate and discuss the application of this tool to quantify a broad spectrum of plant phenotypes/traits such as: tissue culture parameters, ground surface covered by annual plant canopy, root and leaf projected surface area, and leaf senescence area ratio. The software provides easy to use functions to analyze images. While use of involves subjective operator color selections, applying them uniformly to full sets of samples makes it possible to provide quantitative comparison between test subjects. The tool is simple and straightforward, yet suitable for the quantification of biological and environmental effects on a wide variety of visual plant traits. This tool has been very useful in quantifying different plant phenotypes in several recently published studies, and may be useful for many applications.